Repair of Aorto-Right Ventricular Tunnel: A Case Report - Sheikh, Naveen (Cardiovascular Journal, 2010)
Aorto-ventricular tunnel is a congenital, extracardiac channel which connects the ascending aorta above the sinutubular junction to the cavity of the left, or less commonly, to the right ventricle. Here, I report a successful surgical correction of aorto-right ventricular tunnel with anomalous right coronary artery (RCA) arising from the tunnel in a 42 years old woman diagnosed preoperatively with echocardiography and cardiac catheterization. The operation was performed with cardiopulmonary bypass and hypothermia. Myocardial protection was achieved by antegrade cold blood cardioplegia. The tunnel below the origin of RCA was closed with pericardial patch. Tunnel was closed with mattress suture and running stitches to reduce the diameter and making channel for RCA blood flow. Atrial septal defect was closed by patch. The postoperative course was uneventful except pericardial effusion which was managed conservatively. A follow-up transthoracic echocardiogram demonstrated a securely closed communication without any aortic valve incompetence. Keywords: Congenital heart disease; Aorto- RV Tunnel (ARVT). DOI: 10.3329/cardio.v3i1.6435 Cardiovasc. j. 2010; 3(1): 98-100